Pengaruh Asam Parangi (Dialium indium) dan Waktu Marinasi Menggunakan Vacuum Marinator Terhadap Kualitas Organoleptik dan Mikrobiologi Rarit Daging Sapi - Peni Patriani; Harapin Hafid (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
Rarit is a processed product originating from the island of Lombok, in the form of meat sheets that are marinated with salt and sour spices, then dried in the sun. The development of quality and attractive rare products for consumers requires the right method in the use of additives and preservatives because they can affect consumer health. This study aims to analyze the optimization of beef rare quality through the integration of the use of Parangi Acid (Dialium indium) and vacuum marinator technology. The research design used a Completely Randomised Design Factorial (4x2) with 4 replications. The first factor was parangi acid marination level, consisting of 0%, 15%, 30%, and 45%, and the second factor was marination time using a vacuum marinator tumbler (15 minutes and 30 minutes). The results showed that parangi acid and marination time using a vacuum marinator had a significant effect (P?0.05) on microbiological and organoleptic quality. The best treatment was rare marinated using paraffin acid with a concentration of 45% for 15 minutes. Processing rare using parangi acid was effective in improving the organoptic and microbiological quality of rare beef. Parangi acid has potential as a natural preservative in rare beef.